Ivacaftor restores delayed mucociliary transport caused by Pseudomonas aeruginosa–induced acquired cystic fibrosis transmembrane conductance regulator dysfunction in rabbit nasal epithelia. Issue 5 (26th October 2021) - Cho, Do‐Yeon; Zhang, Shaoyan; Skinner, Daniel F.; Lim, Dong Jin; Banks, Catherine; Grayson, Jessica W.; Tearney, Guillermo J.; Rowe, Steven M.; Woodworth, Bradford A.
Abstract : Background: Abnormal chloride (Cl – ) transport dehydrates airway surface liquid (ASL) in sinonasal epithelium leading to mucus stasis and chronic rhinosinusitis. As an experimental epithelium, rabbit tissue provides an excellent representation of human sinus disease, and the rabbit sinusitis model is both established and well suited for therapeutic interventions in vivo. Our objective in this study was to evaluate whether ivacaftor reverses the consequences of Pseudomonas aeruginosa– induced acquired cystic fibrosis transmembrane conductance regulator (CFTR) dysfunction. Methods: Rabbit nasal cavities were assessed for responsiveness to ivacaftor in vivo (by nasal potential difference [NPD] assay). Rabbit nasal epithelial (RNE) cultures were incubated with an ultrafiltrate of P aeruginosa (PAO1 strain) for 4 hours and tested for acquired CFTR dysfunction. Markers of mucociliary function, including airway surface liquid depth (ASL), periciliary liquid depth (PCL), ciliary beat frequency (CBF), and mucociliary transport (MCT), were measured by micro‐optical coherence tomography (μOCT) after PAO1 and/or ivacaftor incubation. Results: Ivacaftor resulted in a significant mean NPD polarization of 21.8 ± 2.1 mV, which was significantly greater than that seen in the low Cl − control (12.9 ± 1.3; p = 0.01). PAO1 exposure induced a state of acquired CFTR dysfunction in rabbit nasal epithelium as measured by forskolin‐stimulated short‐circuit current (ISC ) (control, 37.0 ± 1.1 μA/cm 2 ; PAO1, 24.4 ± 1.1 μA/cm 2 ; p < 0.001). RNE cultures exposed to PAO1 had inhibited mucociliary function, whereas coincubation with ivacaftor restored mucociliary clearance, as measured by μOCT. Conclusion: In rabbit nasal epithelium, ivacaftor robustly stimulates CFTR‐mediated Cl − secretion and normalizes ASL and CBF in PAO1‐induced acquired CFTR dysfunction. Preclinical testing of CFTR potentiators as therapy for P aeruginosa rabbit sinusitis is planned.